IDENTIFIKASI SENYAWA AKTIF ANTIFEEDANT DARI EKSTRAK DAUN PANGI (Pangium Sp) DAN UJI AKTIVITASNYA TERHADAP ULAT KUBIS (Plutella Xylostella) - Putra Mahardika, Ida Bagus; Puspawati, Ni Made; Widihati, Ida Ayu Gede (Jurnal Kimia (Journal of Chemistry), 2014)
Leaves of pangi (Pangium edule) are known to have many benefits, including antifeedant activity. 500 g of pangi leaf powder was extracted by maceration method using n-hexane extract yieled 4.51 g of dark green extract. This extracts showed high antifeedant activity (47.23%) against Plutella Xylostella at a concentration of 0.1% (w / v). Separation of 2 g of n-hexane extract by chromatography column using n-hexane: ethyl acetate: chloroform (6:2,5:1,5) as mobile phase and silica gel 60 as stationary phase produced 6 groups of fractions.  Fractions 3 reveiled the highest antifeedant activity that is 52.15%, 69.88%, and 91.66% respectively at a concentration of 10 ppm, 100 ppm, and 1000 ppm. This active fraction which was considered relatively pure following purity test on TLC was then identified using GC-MS spectrometre. GC-MS spectra of antifeedant active compound contained at least 11 compounds with 8 compounds successfully identified as ? – pinene, benzene trimethyl, acetic acid triflouro-tetradecyl ester, nonadecene, 13-Hexyloxacyclotridec-10-en-2-one, phytol, 3-eicosene, , benzenedicarboxylic acid diisooctyl este.
Keywords: Leaves of pangi, Pangium edule, Plutella Xylostella, antifeedant